Single Visit Endodontics with Related Myths: A Questionnaire - Singh, Shelly; Mehta, Urmi; Rabara, Raj; Mishra, Raman; Sharma, Himanshu; Soni, Bhavana (Journal of Neonatal Surgery, 2025)
Aim: The main objective of performing root canal therapy is to eliminate the bacteria from the root canal and seal it with various newer filling materials. If the treatment is thoroughly done it helps in faster periapical healing. Single visit endodontic treatment had numerous drawbacks primarily about the post-operative pain and failure of the treatment effect. With recent advances in endodontics the single visit therapy has become more predictable and lessened intraoperative procedure and has increased operators comfort. In this review article indications and contraindications of single visit endodontics, success rates and myths related to it are discussed. Single visit root canal treatment is predicted on the entombing theory, which states that the large number of microorganisms are removed during cleaning and shaping and therefore the remaining bacteria are entombed by the root canal obturation, The recent advances, helps the dental practitioners and endodontists to perform the root canal treatment in single visit.